The chain effects of service innovation components on the building blocks of tourism destination loyalty: the moderating role of religiosity - Cheng, Boon Liat *; Nikhashemi, S.R.; Dent, Michael M. * (Emerald, 2020)
Purpose – Having Middle Eastern tourism industry as the context, this study aims to examine the impact of the four main dimensions within service innovation (i.e. product, process, organizational and marketing innovations) on tourist satisfaction; subsequently, towards the development of destination loyalty. Realized that religiosity prevails as an important social force that shapes individual behaviours, this study, hence, placed further assessment upon its moderating role, specifically in the relationships between tourist satisfaction and destination loyalty. Design/methodology/approach – With adopting the approach of self-structured questionnaire, 214 usable responses had been collected for this study. Obtained data was then analyzed by conducting exploratory factor analysis, confirmatory factor analysis and multiple linear regression analysis through the usage of structural equation modelling. Findings – Analysis of obtained data has revealed all the investigated dimensions within service innovation as active predictors to tourist satisfaction, with the exception of product innovation, while having marketing innovation being of highest significance. In turn, tourist satisfaction is found to greatly influence the formation of destination loyalty. Findings then provide notable indication on religiosity as a moderating factor to the proposed relationships within the investigated framework, between service innovation and tourist satisfaction, as well as tourist satisfaction and destination loyalty. Originality/value – This study, thus, revealed the level of religiosity, particularly from the standpoint of Islamic perspectives, in playing a critical role towards predicting capability of service innovation on tourist satisfaction, and further, destination loyalty. Contributions hereby lie on theoretical and pragmatic insights concerning aspects of service and Islamic marketing within today’s tourism front.